Sensing of tryptophan by a non-toxic cobalt(ii) complex. Issue 98 (7th October 2016) - Jana, Swapan Kumar; Mandal, Amit Kumar; Kumar, Anoop; Puschmann, Horst; Hossain, Maidul; Dalai, Sudipta
Abstract : The first report of a cobalt(ii ) based non-toxic, hemocompatible, fluorescent probe that sense Trp and BSA by reducing internal fluorescence quenching of Trp in aqueous solution. Abstract : A non-toxic, hemocompatible, fluorescent probe as cobalt(ii ) based complex [Co(PS)4 ](ClO4 )2 (1 ) (PS: N -pyridylsalicylaldimine) was successfully synthesized and characterised by single crystal X-ray diffraction studies. The structural analysis revealed that1 exhibits intramolecular π–π interaction. The recognition ability of1 towards various amino acids and proteins were studied by UV-vis and fluorescence spectroscopy. The titled complex selectively sense the Trp by reducing its internal fluorescence quenching. It also sense BSA with a detection limit of 56 nM. The binding constant of1 was analysed by Hill's equation and it was found that it binds to Trp and BSA in the order of 10 3 and 10 4 respectively.